Viral and Bacterial Etiology of Common Respiratory Infections in Sub-Saharan Africa: A Review - (:unkn) unknown (My University, 2025)
Background: Respiratory infections are a major public health problem worldwide, with potentially serious consequences. Indeed, these infections remain one of the main causes of morbidity and mortality in children under 5 years old in developing countries. Etiological information on respiratory infections is crucial for prevention and case management strategies. This systematic review aims to describe the etiology of respiratory infections reported in studies carried out in sub-Saharan African countries; (2) Methods: Using PubMed, HINARI and Google scholar search engines, a systematic search was carried out to identify published articles on the etiology of viral and/or bacterial respiratory infections in sub-Saharan Africa in patients of all ages. We have only considered data from sub-Saharan Africa. Papers published from 2010 to 2021, in English or French have been included in this review; (3) Results: After reviewing 115 articles reporting studies carried out in the African continent, only 32 articles were selected of which, studies were conducted in 15 sub-Saharan African countries, including 6/32 (18.75%) in Cameroon. Twenty (62.5%) were cross-sectional studies, and twenty-four (75%) were hospital-based investigations. In these studies, RT-PCR and culture methods were respectively used for viruses and bacteria investigations. Respiratory syncytial virus was the most frequently identified, with prevalence ranging from 0.6% to 59%, followed by rhinovirus (9.3% -73%), influenza virus (flu) A/B (0.9%-69.1%), and human adenovirus (0.9% - 30.8%). Streptococcus pneumoniae (14.2% - 96%), followed by Haemophilus influenzae type b (2.5% - 54%), and Klebsiella pneumoniae (1.4% - 49.9%) were the most frequently detected bacteria; (4) Conclusions: This review has reported that many pathogens, mainly viruses, are associated with acute respiratory infections in sub-Saharan Africa in both children and adults. Unfortunately, the limited geographical distribution of
Keywords: African Research